Optimización de perforación y voladura, con malla de corte cilíndrico en lugar del corte quemado en labores de avance, U.M.- Marsa - García Valverde, Víctor Alfredo (2023)
This work focuses on optimizing drilling and blasting in advance work with 8x9 foot sections, in a type IIIB (Bieniawski) structural rock, in the Valeria I Zone. By replacing the burnt-cut drilling mesh by the perforation mesh with cylindrical cut, designed according to Holmberg's mathematical model. The methodology used in the investigation is of a descriptivecomparative type, the population is composed of the linear work of exploration and development progress, for the data collection the direct observation guide was used. The results obtained were very favorable, managing to increase the advance per shot from 1.89 to 2.08 meters, which represents a 9% increase in advance, going from 83% to 92% efficiency. Likewise, the reduction of drilling and blasting indicators was generated. Decreasing the linear load factor from 23.42 Kg/meter to 19.75 Kg/meter, the volumetric load factor was reduced from 3.53 Kg/m^3 to 3.01 Kg/m^3, reducing the amount of emulsion from 44.36 to 41.10 Kg. In addition, it was possible to reduce the unit costs of drilling and blasting, from S/.948.68 to S/.842.37 per meter, achieving savings of S/.106.31. /m, which represents a decrease of 11.21% of the costs. Similarly, the cost of cleaning was reduced from 95.24 to 93.75 S/. /m and the cost of maintenance from 333.54 to 311.53 S/. /m. Finally, it is determined that by using the cylindrical cut in the perforation mesh it is possible to improve efficiency, which represents an increase in performance and a decrease in costs per shot.